La discalculia en el rendimiento académico en el área de matemática de los niños de quinto grado de educación general básica paralelo “c” de la unidad educativa “Chunchi” cantón, Chunchi provincia Chimborazo período lectivo 2014-2015 - Izurieta Jara, Verónica Isabel (2016)
Referring to the academic field for the improvement and quality of education is required to work with professional and updated mystique by each of the teachers, the educational needs of students lead to a radical change in the teaching learning in education centers. Considering all this background consideration gets a profound study whose primary objective is to determine the problems of dyscalculia, affecting significantly in academic performance in the area of mathematics of fifth graders of basic general education in the Educative Unit Chunchi, it is exposed to clearly and precisely point conceptualizations on the subject, making a crossing by different ideas of different authors and works that approach the subject from different positions, a listing considered for defining basic terms so that there is a better understanding , the hypothesis arisen from the s research is exposed, taking into account the two variables of the same study that allowed us to operationalize. For this research were considered various methods such as the scientific, inductive, deductive, analytical and synthetic which have served as guide and orientation for the study. The research is exploratory, descriptive, explanatory and bibliographical type, the design is quasi-experimental since children were observed when applying the brochure. The population is composed of 35 students. The techniques have been used as instruments of observation and the observation sheet is structured with 10 items, it has been managing a procedure for tabulating using tables and pies to perform the examination. Similarly conclusions are established based on the obtained results which takes into account the criteria issued by the investigating interpretations. Bibliographical sources and the respective annexes are presented where the proposal is submitted with the development of a guide of activities that encourage solving the problem under study.